y2+0y-1=0

Multiply 0 by y.

y2+0-1=0

Add y2 and 0.

y2-1=0

y2-1=0

Add 1 to both sides of the equation.

y2=1

Take the square root of both sides of the equation to eliminate the exponent on the left side.

y=±1

Any root of 1 is 1.

y=±1

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

y=1

Next, use the negative value of the ± to find the second solution.

y=-1

The complete solution is the result of both the positive and negative portions of the solution.

y=1,-1

y=1,-1

y=1,-1

Solve for y y^2+0y-1=0